Transdermal Delivery of Ketoprofen for Osteoarthritis Treatment and Management: A Literature Review on Current Progression - Ramadhani, Dwi Asih; Harahap, Yahdiana; Sagita, Erny; Permata Sari, Kartika Citra Dewi; Andranilla, Rr. Kirana; Trisina, Jessica; Punu, Gabriella Frederika; Ramadon, Delly (UI Scholars Hub, 2024)
Arthritis, a diverse spectrum of joint disorders, is characterized by chronic pain and inflammation. Osteoarthritis (OA), the most prevalent form, leads to disabling pain, functional limitations, and reduced mobility. Nonsteroidal anti-inflammatory drugs (NSAIDs) are widely used for managing OA pain, with ketoprofen recognized as one of the effective options. However, oral administration of ketoprofen may cause gastrointestinal irritation. Addressing this issue, Transdermal Drug Delivery Systems (TDDS) emerge as a promising alternative route of administration. TDDS facilitates delivery of various drugs through the skin without undergoing first-pass metabolism. Recent studies have centered on enhancing ketoprofen’s transdermal delivery, particularly focusing on different methods (such as patches, gels, electroporation technology, and stratum corneum bypass methods), with microneedles emerging as a promising approach for delivering anti-inflammatory drugs through transdermal routes. This review aims to explore recent advancements in transdermal drug delivery systems for managing OA. The utilization of transdermal ketoprofen presents innovative opportunities for future research and development in novel drug delivery systems.